Exploring Opportunities and Threats in Logistics and Supply Chain Management of Thai Fruits to India - Roengchai Tansuchat; Suthep Nimsai; Pairach Piboonrungroj (International Journal of Supply Chain Management, 2016)
Recently countries are gaining opportunities and confronting confront obstacles arising from global supply chain integration. The main objective of this paper is to explore business opportunities and threats in terms of logistics and supply chain management of exporting Thai fruits to India. Supply Chain Analysis (SCA) framework is used to analyse the business opportunities and logistics management in India market in schemes run by the modern trade to assist smallholders with production and marketing. The study, consequently, intends to explore empirically the pattern of Thai fruits supply chain management and restructuring in India market. The patterns of logistics and supply chain management found in this study are substantiated and linked with the existing modern trade scheme to see whether there are inconsistencies in the policies and actual implementations. This presents threats as well as opportunities for smallholders in Thailand. The standard set by buyers requires farmers to adjust their production and marketing systems. Assistances for farmers are derived from modern trade and government and collaborations amongst these two parties. MICE is proposed to be a mechanism to promote opportunities of exporting Thai fruits to India.